O processo de criação de conhecimento em empresas localizadas em clusters industriais: um estudo multi-caso no setor de biotecnologia na França e no Brasil - Ferasso, Marcos (2008)
The process of knowledge creation (CC) is crucial to an enterprise whereas it identifies, transforms and creates tangible and intangible assets that are mobilized on behalf of innovations. Enterprises look to overcome limitations that interfere in this process and one of the ways resides in the localization of industrial clusters (CIs). The lack of literary work unleashed the interest on focusing this research in the CC process in localized CIs companies. The present research intends to understand how the knowledge creation process of internal level is structured in participant enterprisers of biotechnological-industrial clusters in France and Brazil. The biotechnological sector is based on the nature of technological frontier. Because the CC process is dynamic we have chosen cluster enterprises that featured this phenomenon, especially the Bioméditerranée cluster (Marseilles, France) and the Belo Horizonte cluster (Brazil). This work is a study of multiple cases with an inferential and exploratory approach. Thereafter the structuring of the theme and data collection, they were reduced, cut out and synthesized to a subsequent use of standard techniques, adaptation and synthesis of crossed cases from logical models of organization levels, which drove us in a typology of a general case, in a framework shape. The empirical evidences have showed that, however the internal CCs procedures are similar to its structure while a process, the differential to obtain new acquirements and changes are the tangible and intangible assets that are available in each enterprise and the assets which can be attracted by its external connections. Considering the frontier knowledge that was chosen to observe the phenomenon, the enterprise relations with cluster is a factor of internal processes acceleration, because cluster promotes various accesses to a social environment, providing knowledge assimilation to its members. The professional’s highly qualified knowledge in each company establishes what we call core knowledge, which allows the access to new innovations and discoveries, usually commercialized in the extra-cluster level. The enterprises which obtained diverse incentive and investment, notably from the government and its spheres, have had significant increments in its CCs processes mainly because these increments have provided reduction of costs. Clusters aid multiply assets that are used to reduce costs, to accelerate internal process and improve existent information in the company. The theoretical implication of the present research settles in identifying processes, strategies and qualifiers being considered beforehand and afterwards in a CC process. As management implications, it was noted that enterprises which are inserted in CIs seek internal processes’ factors of acceleration because of the assets accessed by CIs, which allow companies to acquire innovations in a faster way. Also, as a suggestion to future researches, it is recommended the replication of this work to other economical sectors.